Locke a very short introduction. - Dunn, John (Oxford Oxford University Press, 2003)
John Locke (1632-1704) one of the greatest English philosophers of the late seventeenth and early eighteenth century, argued in his masterpiece, An Essay Concerning Human Understanding, that our knowledge is founded in experience and reaches us principally through our senses; but its message has been curiously misunderstood. In this book John Dunn shows how Locke arrived at his theory of knowledge, and how his exposition of the liberal values of toleration and responsible government formed the backbone of enlightened European thought of the eighteenth century. ABOUT THE SERIES: The Very Short Introductions series from Oxford University Press contains hundreds of titles in almost every subject area. These pocket-sized books are the perfect way to get ahead in a new subject quickly. Our expert authors combine facts, analysis, perspective, new ideas, and enthusiasm to make interesting and challenging topics highly readable.
Shows how John Locke, a great English philosopher of 18th century, arrived at his theory of knowledge. This work also shows how the liberal values of toleration formed the backbone of European thought of the 18th century. It looks at the questions which he addressed with such tenacity: 'how Man can know' and 'how Man should try to live'.
3. Knowledge, belief and faith
Keywords: Locke, John -- 1632-1704.; Philosophy, English -- 17th century